2007
DOI: 10.1175/jpo3005.1
|View full text |Cite
|
Sign up to set email alerts
|

Is the World Ocean Warming? Upper-Ocean Temperature Trends: 1950–2000

Abstract: Subsurface temperature trends in the better-sampled parts of the World Ocean are reported. Where there are sufficient observations for this analysis, there is large spatial variability of 51-yr trends in the upper ocean, with some regions showing cooling in excess of 3°C, and others warming of similar magnitude. Some 95% of the ocean area analyzed has both cooled and warmed over 20-yr subsets of this period. There is much space and time variability of 20-yr running trend estimates, indicating that trends over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 16 publications
6
36
0
Order By: Relevance
“…It turns out that observed density shows increasing trends particularly in the western part of the tropical Pacific. This is consistent with observed temperature decreases in this region (Harrison and Carson, 2007). Hence density trends at 300 dbar differ between model and observations, but as they are primarily related to warming and with solubility changes contribution little to the total DO trends (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It turns out that observed density shows increasing trends particularly in the western part of the tropical Pacific. This is consistent with observed temperature decreases in this region (Harrison and Carson, 2007). Hence density trends at 300 dbar differ between model and observations, but as they are primarily related to warming and with solubility changes contribution little to the total DO trends (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…and AchutaRao et al (2006) instead sampled models to mimic the Levitus et al (2001) calculation and found large discrepancies between global and hemispheric averages, including, in the former, sign reversals [somewhat in conflict with the results of Barnett et al (2001)]. Harrison and Carson (2007) discuss the great difficulties in inferring global upper ocean averages from the data after 1950 and call attention to the need for far better understanding of the accuracies of quoted subglobal averages.…”
Section: ) Lower Bounds On the Sampling Errorsmentioning
confidence: 88%
“…A number of recent studies (e.g., Harrison and Carson 2007;Cravatte et al 2009) describe limitations imposed by poor historical data records in temperature and salinity observations for the global and Pacific Oceans, respectively. However, these studies analyze the ocean in small spatial bins, increasing the chance of noise swamping a broad-scale trend signal.…”
Section: Significance Of Resolved Trendsmentioning
confidence: 99%